Enlarged parietal foramina: a case report - Mariana Gaspar; Susana Moleiro; Carla Conceição; Amets Sagarribay (Publicaciones Permanyer, 2023)
Enlarged parietal foramina is a rare entity that results from late or incomplete ossification, ending as large foramina in the parietal bone. Usually, affected children are asymptomatic but may present with severe headache, vomiting or predisposition for epilepsy. This case aims to raise awareness of a rare clinical entity that can be manifested by a persistently opened posterior fontanelle. The prognosis is mostly benign.